2009
DOI: 10.1093/jb/mvp206
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of dihydrofolate reductases from deep-sea bacteria

Abstract: Enzymes from organisms living in deep-sea are thought to have characteristic pressure-adaptation mechanisms in structure and function. To better understand these mechanisms in dihydrofolate reductase (DHFR), an essential enzyme in living cells, we cloned, overexpressed and purified four new DHFRs from the deep-sea bacteria Shewanella violacea (svDHFR), Photobacterium profundum (ppDHFR), Moritella yayanosii (myDHFR) and Moritella japonica (mjDHFR), and compared their structure and function with those of Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 40 publications
3
32
0
Order By: Relevance
“…Under a pressure of 200 MPa, no activities were observed in this study (data not shown), although the soluble enzymes retained 30-60% of their activities under similar conditions. [15][16][17] The reason for this remains unclear, but it is possible that the presence of membrane lipids affects enzyme properties under high pressure. On the other hand, shifts in growth temperature showed no effect on the response of respiratory terminal oxidase activity to pressure and temperature (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under a pressure of 200 MPa, no activities were observed in this study (data not shown), although the soluble enzymes retained 30-60% of their activities under similar conditions. [15][16][17] The reason for this remains unclear, but it is possible that the presence of membrane lipids affects enzyme properties under high pressure. On the other hand, shifts in growth temperature showed no effect on the response of respiratory terminal oxidase activity to pressure and temperature (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, many of the soluble enzymes of piezophiles have been found to be relatively resistant to high pressure. [15][16][17] Hence it is of interest to identify the most critical factors in maintaining the activity of membrane-associated enzymes under high pressure. Is it the properties of membranes and their interaction with proteins, or characteristics of the proteins themselves, that is of paramount significance in this regard?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that the catalytic activity of DHFR from Moritella yayanosii, which is 95 % identical to MpDHFR, has a pH dependence very similar to that reported here for MpDHFR. [43] The K M for both cofactor and substrate varied slightly with pH, with maximum values around physiological pH (Figure 7 B and C). The K M values for DHF are small compared to those for NADPH, although the K M values for both ligands are relatively small at low temperature and pH, and at high pH.…”
Section: Kinetic Analysis: the Effect Of Temperaturementioning
confidence: 95%
“…Essential proteins must have adapted to the species habitat (19)(20)(21)(22)(23)(24)(25). Adaptation means the preservation of the functionality of proteins.…”
mentioning
confidence: 99%